Practices of Looking: An Introduction to Visual Culture - Marita Sturken; Lisa Cartwright (New York Oxford University Press, 2017)
Practices of Looking, Third Edition, bridges visual, communication, media, and cultural studies to investigate how images and the activity of looking carry meaning within and between different arenas in everyday life. The third edition has been updated to represent the contemporary visual cultural landscape and includes topics like the increasingly rapid global circulation of media, the rise of design and DIY cultures, digital media art and activism, and challenges to photojournalism and news media. Challenging yet accessible, Practices of Looking, Third Edition, is ideal for courses across a range of disciplines.
Keywords: Nonfiction; Art; Textbooks; Theory; Sociology; Art history; Academic; Philosophy; Photography; Visual communication; Popular culture; Art and society; Culture; Visual perception; Communication and culture; (FSD140) Introduction to Design Practice and Fashion Promotion